On generic placement of Odynerus dictatorius Giordani Soika and its mimicry ring (Hymenoptera: Vespidae: Eumeninae) - Selis, Marco (Zootaxa, 2020)
The generic placement of Odynerus dictatorius Giordani Soika, 1935 is discussed (Antodynerus dictatorius comb. nov.) and three new species belonging to its mimicry ring are described: Antodynerus breviclypeus sp. nov., Antodynerus imitator sp. nov. and Antepipona dictatoria sp. nov.